Respuesta :

So I would use elimination to solve this
4x-2y= -2
3x+2y= -12
The 2y cancel out

7x=-14
7. 7

X equals -2

Plug that back in

3(-2)+2y=-12

-6+2y=-12
+6. +6

2y=-6
2. 2


So the point of intersection is (-2,-3)

Answer:

x=-2

y=-3

Step-by-step explanation:

4x-2y= -2

3x+2y= -12

This is a simultaneous equation, which can be solved using either the elimination method or the substitution method. But for the purpose of this question, we would be using the elimination method.

4x-2y= -2 Equation 1

3x+2y= -12 Equation 2

Since, y in both equations has the same coefficient, we can easily eliminate it by adding both equations together.

4x+3x=7x

-2y+(+2y)= -2y+2y=0

-2+(-12)=-2-12=-14

We now have

7x=-14

x=-14/7

x=-2

We substitute x with -2 in any of the equations to get y. Let's take equation 2

3x+2y= -12

3(-2)+2y=-12

-6+2y=-12

2y=-12+6

2y=-6

y=-6/2

y=-3